SAT0316 Key Role of Cardiac Biomarkers in the Assessment of Systemic Sclerosis: Contribution of High Sensitivity Cardiac Troponin. (10th June 2014) - Avouac, J.; Meune, C.; Chenevier-Gobeaux, C.; Borderie, D.; Lefevre, G.; Kahan, A.; Allanore, Y.
Abstract : Background: Microangiopathy is a cardinal feature of systemic sclerosis (SSc), which plays a critical role in the development of primary myocardial involvement and pulmonary hypertension, two major causes of death in SSc. Objectives: Our aim was to measure plasma concentrations of two cardiac biomarkers, high sensitive Cardiac troponin T (HS-cTnT), a marker of myocyte necrosis and/or ischemia, and N-terminal fragment of pro-BNP (NT-proBNP), a marker of cardiac strain, in two large cohorts of SSc patients and controls. Methods: 161 SSc patients (135 women, 84%) with a mean ± SD age of 57±17 years were included and were compared to 213 healthy controls (170 women, 80%, mean ± SD age of 55±11 years). The plasma HS-cTnT concentrations were measured using an electrochemiluminescence immunoassay (Roche Diagnostic, Meylan, France). The 99th percentile, with a CV ≤10% was achieved for 14 ng/L. Plasma NT-proBNP levels were assessed by an immunoenzymatic assay (Roche Diagnostic). Results: Among the SSc cohort, mean disease duration was 9±8 years, 65 patients (40%) had the diffuse cutaneous subset. HS-cTnT and NT-proBNP plasma levels were significantly increased in SSc patients versus controls (p=0.0001 and p<0.0001 respectively). SSc patients were more likely to have above the cut-off value concentrations of HS-cTnT (>14 ng/L) and NT-proBNP than controls (30/161 patients (19%) with HS-cTnT >14 ng/l vs. 4/213 controls (2%), p<0.0001; 17/161 patients (11%) with increased NT-proBNP levels vs. 8/213 controls (4%), p=0.02). Similar results were observed in the subgroup of patients free of any cardiovascular risk factors. Multivariate logistic regression analysis confirmed diabetes mellitus (p=0.006), high blood pressure (p=0.02), precapillary pulmonary hypertension (PH) (p=0.04), ESR >28 mm/H1 (p=0.007) and the diffuse cutaneous subset (p=0.004) as factors independently associated with HS-cTnT >14 ng/L. Increased NT-proBNP concentrations were only associated with the presence of precapillary PH (p=0.0001). The combination of increased HS-cTNT and NT-proBNP levels had the highest positive predictive value for the diagnosis of precapillary PH (67%) compared to HS-cTnT (20%) or NT-proBNP (35%) alone. Conclusions: Plasma levels of HS-cTnT and NT-proBNP are increased in SSc patients. Associated factors with increased HS-cTnT include the diffuse cutaneous subset and precapillary PH, which reflect the severity of the disease. In addition, the combination of increased HS-cTnT and NT-proBNP plasma concentrations display higher positive predictive value for the diagnosis of precapillary PH than each marker alone. Given the prognostic significance of these biomarkers, they might be helpful to select the patients that justify further examinations in case of suspicion of cardiac complication. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4011